2020
DOI: 10.3389/fnagi.2020.00217
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Mechanisms Linking Diabetes Mellitus and Alzheimer’s Disease: the Receptor for Advanced Glycation End Products (RAGE)

Abstract: Diabetes and Alzheimer's disease (AD) place a significant burden on health care systems in the world and its aging populations. These diseases have long been regarded as separate entities; however, advanced glycation end products (AGEs) and the receptors for AGEs (RAGE) may be a link between diabetes and AD. In our study, mice injected with AGEs through stereotaxic surgery showed significant AD-like features: behavior showed decreased memory; immunofluorescence showed increased phosphorylated tau and APP. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 66 publications
2
38
0
1
Order By: Relevance
“…RAGE is a 35 kDa protein in the immunoglobulin superfamily, and its increased expression can lead to in ammatory conditions [23,32]. In the case of asthma, the close relationship between RAGE overexpression and asthma development has been reported previously by ourselves and others [22,23,33,34]. In the present study, we observed that RAGE is up-regulated in PBMCs from asthma patients, which was consistent with its previously reported expression pattern [22].…”
Section: Discussionsupporting
confidence: 92%
“…RAGE is a 35 kDa protein in the immunoglobulin superfamily, and its increased expression can lead to in ammatory conditions [23,32]. In the case of asthma, the close relationship between RAGE overexpression and asthma development has been reported previously by ourselves and others [22,23,33,34]. In the present study, we observed that RAGE is up-regulated in PBMCs from asthma patients, which was consistent with its previously reported expression pattern [22].…”
Section: Discussionsupporting
confidence: 92%
“…There is evidence showing that AGEs specific receptors (RAGEs), which are found in neurons, microglia, astrocytes, and vascular endothelial cells, interacts not only with AGEs, but also with Aβ and mediate inflammatory effects [ 309 ]; it is even described that RAGEs could mediate Aβ transport through blood brain barrier (BBB) or enhance expression of BACE1, thus promoting Aβ formation [ 310 ]. It has been proved that AGEs could induce tau hyperphosphorylation through RAGEs-GSK3β signaling activation [ 311 ], and direct AGEs injection in mice brain displayed AD pathological features, such as decreased memory and increased tau phosphorylation, APP expression, and Aβ 42 formation [ 312 , 313 ].…”
Section: The Relation Between T2dm and Ad: A Molecular Approachmentioning
confidence: 99%
“…The long-live proteins are preferentially modified to form AGEs and the high stability of Aβ makes it an ideal substrate for non-enzymatic glycation and formation of AGEs. A role of blood sugars would also explain the link observed between the apparently unrelated diabetes and AD; diabetic patients have a 2-5-fold higher tendency to develop AD compared with nondiabetic individuals [ 54 , 55 , 56 , 57 , 58 ].…”
Section: Glycation Role In Amyloid Aggregationmentioning
confidence: 99%